Early diagnosis of cervical cancer and gynecological problem - Bedoya Hevia, Mariano (1956)
The early diagnosis of cervical cancer remains a gynecological problem that requires an immediate solution; because we continue to see with surprise that the highest rate of cancer mortality in women occupies cervical cancer; This is undoubtedly due to the ill treatment reach an advanced level of disease; recognizing that late diagnosis is still made, however great concern and interest shown by medical researchers to overcome techniques to achieve early diagnosis and if we add to all this propaganda organized by the state, we see that there is very little that has been obtained in relation to the great effort made. This is the reason I am going to present for the consideration of all of you. Progress on semiotic technique has been achieved so far to get to early diagnosis and personal contribution in more than 15 years of observation.